Chromosome-specific sequencing reveals an extensive dispensable genome component in wheat - Liu, Miao; Stiller, Jiri; Holušová, Kateřina; Vrána, Jan; Liu, Dengcai; Doležel, Jaroslav; Liu, Chunji (Scientific reports, 2016)
The hexaploid wheat genotype Chinese Spring (CS) has been used worldwide as the reference base for wheat genetics and genomics, and significant resources have been used by the international community to generate a reference wheat genome based on this genotype. By sequencing flow-sorted 3B chromosome from a hexaploid wheat genotype CRNIL1A and comparing the obtained sequences with those available for CS, we detected that a large number of sequences in the former were missing in the latter. If the distribution of such sequences in the hexaploid wheat genome is random, CRNILA sequences missing in CS could be as much as 159.3 Mb even if only fragments of 50 bp or longer were considered. Analysing RNA sequences available in the public domains also revealed that dispensable genes are common in hexaploid wheat. Together with those extensive intra- and interchromosomal rearrangements in CS, the existence of such dispensable genes is another factor highlighting potential issues with the use of reference genomes in various studies. Strong deviation in distributions of these dispensable sequences among genotypes with different geographical origins provided the first evidence indicating that they could be associated with adaptation in wheat.
Keywords: Sequence Analysis, DNA; Chromosome Mapping; polyploidie; Triticum; Chromosomes, Plant; Polyploidy; sekvenční analýza DNA; pšenice; Genome, Plant; genom rostlinný; chromozomy rostlin; mapování chromozomů